The logic of language - Seuren, Pieter A. M. (Oxford : Oxford University Press, 2009)
This text opens a new perspective on logic. After analyzing the functional adequacy of natural predicate logic and standard modern logic for natural linguistic interaction, the author develops a general theory of discourse-bound interpretation covering such topics as discourse incrementation, anaphora presupposition, and more.
Includes bibliographical references and index.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Language and logic; Psycholinguistics; Semantics